Perceived Visual Enjoyment Factor in Artistic Playability : In Case Study Real Time Strategy (RTS) Game - Ahmad Azaini, Bin Abdul Manaf; Jaibi, Sabian (Blue Eyes Intelligence Engineering & Sciences Publication, 2019)
Each game has their own unique feature, which attracts gamers by constantly playing the game daily. The game appeal also regards the interface attributes, Game mechanics, and interfaces as a factor towards excitement in playing the game. Nevertheless, there is limited discussion pertaining to perceived visual enjoyment factor in artistic playability, especially among youth based on the Real Time Strategy (RTS) game to support the statement. For this purpose, Defence of the Ancients 2 (DOTA 2) were used as a case study as inspired game play. The game according to gamers is essential for each level to deliver challenges that encourage the gamers themselves as motivational goal. In contrary in winning factor, there are also aspects of UX indicates substantially important as the game experience, that is: anatomy of function, and menus, plays important role in achieving goals, especially for the gamers. Therefore, this paper discusses the components of successful game. Method: The sample was tested using System Usability Scale (SUS) for interviews and questionnaire. Despite of a small sampling, SUS is trusted with its accuracy and reliability, also has established an industry standard, with numerous previous references. Based on findings, the online questionnaire distribution (N=10) Results: The result indicates that the players were satisfied with the mechanics of the game, comparatively, the player felt enthusiastic with the competitive challenge to finish the game, and to achieve their objectives. The findings in the paper also established that the visual was not the driven factor for the user’s engagement in continuously playing the game, but desire to complete the challenge in order to gain satisfaction upon completion. The significant finding in this article, that DOTA 2 game largely by definition depends on CTPM (Critical Thoughts Per-Minutes) and communication within the team because critical thinking is highly required in other to perceive the enjoyment; but the intensity, breadth, and acceleration also significantly